The Relationship Between Social Support And Public Anxiety In Facing The Covid-19 Pandemic In Environment II Tangkahan Village, Medan Labuhan Subdistrict In 2021 - Lindawati Simorangkir; Samfriati Sinurat; Murni Sari Dewi Simanullang; Rizka Oktavianty Hasugian (Institute of Computer Science (IOCS), 2021)
Social support is assistance obtained from people around the environment whose relationship is helpful and has own meaning for the person who receives it.. Anxiety is a feeling worried about uncertain characterized by feelings of fear and other responses. Currently social support is needed, with social support can think positively and minimize anxiety faced. This study aims to determine the relationship between social support and public anxiety in facing COVID-19 pandemic in Environmental II Tangkahan Village, Medan Labuhan Subdistrict 2021. This research is a cross- sectional study, with 73 respondents. Sampling was done by purposive sampling technique, is technique of collecting samples with certain considerations or criteria. With criteria: ready to be a respondent, aged 25-55 years, respondent is in good health and cooperative. The results showed 79.5% of social support in enough categories and 67.1% moderate anxiety. Statistical test results show the value of p-value = 0.041 (p<0.05) with r = -0.24, which means that there is a negative relationship between social support and public anxiety in facing COVID-19 pandemic in Environment II, Tangkahan Village. Medan Labuhan District in 2021. Respondents expected to pay more attention and mutual care during this pandemic and always obey to the health protocol to reduce anxiety during a pandemic COVID-19